Synthesis of 5-(phenoxymethyl)-4-R-alkylthio-1,2,4-triazoles and its further oxidation to 3-alkylsulfonylderivatives - Yu. M. Kucheryavyi; A. G. Kaplaushenko; F. Al Zedan (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The rapid development of new "civilization diseases" is one of the negative manifestations of modern technological progress. These diseases include obesity, atherosclerosis, allergy, depression and others. Some of them are still difficulty treated. This fact significantly affects the level of human development. The cause of the problem is the lack of basic researches and the lack of medicines for treatment. Considering these facts, scientists of medical and pharmaceutical industry are working on actual problems.